Aplikasi Pengaduan dan Maintenance Elektronik Berbasis Web dengan Metode First in First Out (FIFO) di Universitas Nasional - Iman Cahyadi; Iskandar Fitri; Nurhayati Nurhayati (KITA Institute, 2022)
The BRT unit is a part of the National University that manages electronic equipment including repairing or maintenance in the event of a breakdown. Usually, BRT unit technicians carry out the process of repairing electronic equipment based on complaints received from staff/employees. However, so far the complaint process is still manual and recorded using simple tools such as excel, word and ledgers. This causes the process of electronic complaints and maintenance to be slow. Therefore, in this study, a web-based electronic complaint and maintenance application will be developed at the National University. The application was developed based on the waterfall model using the PHP programming language and using a MySQL database using the First in First Out (FIFO) method. The results of this study are the availability of applications that can help the processing of electronic complaints and maintenance data to be more effective and efficient. Testing of the application was carried out using the White-box and Black-box methods and testing on 3 flowcharts including the Staff/Employee Logic flowchart, Admin Logic flowchart and Technician Logic flowchart with white-box testing calculated cyclomatic complacity and resulted in Cyclomotic Complexity = 8, Region = 8 with path Independent Path = 8 where the result shows that all the logic and functionality of the application has been running well.